2003
DOI: 10.5134/176311
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Mass Release of Mature Medusae from the Hydroid Halocordyle disticha (Hydrozoa, Halocordylidae) and Experimental Induction of Different Timing by Light Changes

Abstract: The timing mechanism for synchronous mass release of mature medusae of Halocordyle disticha was studied, using colonies from Shirahama, Wakayama, Japan, which were kept in a 450 I aquarium tank. In near natural conditions medusa release is correlated with sudden drop of light intensity such as occurs around sunset. Timing could be manipulated by controlling light intensity. Artificial sunset 2 hours earlier than normal caused mass release of medusae earlier than under natural conditions, whereas sunset artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…It can be expected that the release time of E. japonica would not change if the sunset time is artificially delayed or advanced through artificial lighting. This is in contrast to results obtained by Genzano & Kubota (2003) for another hydroid, Halocordyle disticha . Although our observation periods do not cover the whole reproductive season (June–November; see Kubota, 1994), it can be assumed that the release time remains constant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It can be expected that the release time of E. japonica would not change if the sunset time is artificially delayed or advanced through artificial lighting. This is in contrast to results obtained by Genzano & Kubota (2003) for another hydroid, Halocordyle disticha . Although our observation periods do not cover the whole reproductive season (June–November; see Kubota, 1994), it can be assumed that the release time remains constant.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, other hydrozoans such as Halocordyle disticha (Goldfuss) and Millepora species begin to release their short-lived, mature medusae at about sunset and the release is continued for several hours thereafter. The release is immediately followed by spawning in order to maximize fertilization success (Song & Cho, 1998;Genzano & Kubota, 2003). Eugymnanthea species spawn in the morning hours (Kubota, 2004;Govindarajan et al, 2005), therefore the release of medusa is not synchronized with the time of spawning of the gametes.…”
Section: Discussionmentioning
confidence: 99%
“…Gonophores are eumedusoids, sometimes remaining fixed and sometimes liberated from the hydroid (Hargitt 1900;Brinckmann-Voss 1970). When released, the free eumedusoids are short-lived (surviving a few hours at most) and liberated during evening hours (Hargitt 1900;Baker 1936;Brinckmann-Voss 1970;Calder 1988;Genzano & Kubota 2003). Hoover (1998Hoover ( , 2006 reported that colonies reach about 12 inches (30 cm) high in Hawaii, and specimens up to 22 cm high were observed during this study on a pier at the Hawaii Institute of Marine Biology on Coconut Island in Kaneohe Bay.…”
Section: Fig 43mentioning
confidence: 73%
“…Medusae are seasonally produced in a synchronized fashion by the benthic polyps (Boero & Bouillon, 1993), but the cues triggering medusa production (and therefore their blooms) are unknown in most species. Circannual rhythms, temperature, salinity, moon phases, dissolved oxygen, and water turbidity have all been proposed as possible cues, but have only been tested on few individual species (Brock, 1975; Genzano & Kubota, 2003; Ma & Purcell, 2005; Stefani, 1956; Werner, 1954; Werner, 1961; Nowaczyk et al, 2016; Wintzer, Meek & Moyle, 2013). Upwelling, which often correlated with high productivity, has also been linked to medusa blooms in tropical waters (Miglietta, Rossi & Collin, 2008).…”
Section: Introductionmentioning
confidence: 99%